Long-term results of hearing preservation cochlear implant surgery in patients with residual low frequency hearing. (4th May 2017) - Moteki, Hideaki; Nishio, Shin-ya; Miyagawa, Maiko; Tsukada, Keita; Iwasaki, Satoshi; Usami, Shin-ichi
Abstract: Conclusion: Differences were found between patients with stable hearing and those with progressive hearing loss in the lower frequencies with respect to the rate of progression in the contralateral ear. It is suggested that the electric acoustic stimulation (EAS) can provide improvement in hearing ability over the long-term if residual hearing might be lost to some extent. Objective: To evaluate the long-term threshold changes in the low frequency hearing of the implanted ear as compared with the non-implanted ear, and the hearing abilities with EAS along with the extent of residual hearing. Methods: Seventeen individuals were enrolled and received the EAS implant with a 24-mm FLEXeas electrode array. Hearing thresholds and speech perception were measured pre- and post-operatively for 1–5 years. Post-operative hearing preservation (HP) rates were calculated using the preservation numerical scale. Results: The average linear regression coefficient for the decline in hearing preservation score was −6.9 for the implanted ear and the patients were subsequently categorized into two groups: those with better than average, stable hearing; and those with worse than average, progressive hearing loss. EAS showed better results than electric stimulation alone, in spite of an absence of speech perception with acoustic stimulation.